A theory of firm opacity and corporate social responsibility - You, Linqing; Chen, Zhuoqiong (Journal of Banking & Finance, 2022)
We investigate theoretically the effect of firm opacity, the degree of information asymmetry between firms and outside investors, on whether Corporate Social Responsibility (CSR) activities signal firm value. In our model, a profit-maximizing firm chooses whether to conduct costly CSR activities observable to potential investors and whether to undertake internal corporate and managerial actions that improve its value, which is unobservable to potential investors. We show that the firm is more likely to perform CSR when it undertakes the value-enhancing internal actions in equilibrium, and hence, CSR signals the firm’s value and increases investors’ expected valuation of the shares, only when the firm is moderately opaque. Empirical implications regarding the effect of firm opacity on the correlation between CSR and firm value are discussed.